Framework for Aboriginal-guided decolonizing research involving Métis and First Nations persons with diabetes - Bartlett, Judith G.; Iwasaki, Yoshitaka; Gottlieb, Benjamin; Hall, Darlene; Mannell, Roger (Social Science & Medicine, 2007)
« This paper documents the process of implementing an Aboriginal-guided research approach to examining the lived experiences of Metis and First Nations peoples with diabetes in Winnipeg, Manitoba, Canada. A newly developed Aboriginal-oriented process framework for decolonizing research includes, in order of application, the six processes of rationalizing, enabling, facilitating, experiencing, accepting, and enacting decolonizing research. We review the key methodological elements of our research as a basis for discussing this decolonizing process framework that challenges traditional western ways of doing research, and requires the reformulation of underlying assumptions and methods. Aboriginal-grounded decolonizing research processes have implications for health researchers and health service providers who work with Indigenous peoples worldwide and are particularly useful for developing culturally grounded, communitybased health promotion programs for Indigenous peoples suffering from health-related problems, including diabetes » [Résumé original]. On y trouve notamment un graphique sur des modalités de décolonisation des recherches, ainsi que plusieurs arguments réitérant l'importance de développer des pratiques de recherche culturellement adaptées [Résumé équipe ORPCC]
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; autochtones; décolonialisme; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; recherche collaborative; recherche en milieux de pratique; recherche participative; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions

La recherche partenariale : le modèle de l'ARUC-ÉS et du RQRP-ÉS - Sutton, Louise (L'alliance de recherche universités-communautés en économie sociale et le Réseau québécois de recherche partenariale en économie sociale, 2007)
« Présentation des caractéristiques et des conditions qui facilitent la recherche partenariale en économie sociale, selon le modèle développé par l’ARUC-ÉS et le RQRP-ÉS. L’Alliance de recherche universités-communautés en économie sociale (ARUC-ÉS) et le Réseau québécois de recherche partenariale en économie sociale (RQRP-ÉS) sont des organismes partenariaux de recherche financés par le Conseil de recherches en sciences humaines du Canada (CRSH). Ce consortium de recherche en économie sociale réalise des activités de réflexion, de recherche et de valorisation des connaissances en économie sociale. Ses actions contribuent à la reconnaissance et à l’essor de l’économie sociale comme outil de développement social, culturel, politique et économique du Québec » [Résumé original]
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; québec; recherche en milieux de pratique; recherche partenariale; ressource en ligne; régions géographiques